2007
DOI: 10.1007/bf03026469
|View full text |Cite
|
Sign up to set email alerts
|

Constructivist research in educational technology: A retrospective view and future prospects

Abstract: Along with a socially urgent impetus for revolutionary reform of an educational environment appropriate to the 21st century society, constructivism is highlighted in various fields related to education as an alternative educational ideology and approach. Despite its radical shift from traditional learning environments, and the diverse interpretation and understanding among scholars on the nature of constructivism, constructivism surely has brought out meaningful changes and developments in understanding how pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Journal of Research on Technology in Education,38(4), General education researchers have also suggested instructional approaches to embed within a single-course to enhance learning. One suggestion is to create a constructivist-based learning environment that promotes hands-on learning, collaboration, and modeling (Kang, Choi, & Chang, 2007). The merits of constructivist-based learning environments include: exposing pre-service teachers to authentic learning tasks (Murphy, 1997), improving pre-service teachers' perception of technology (Vannatta & Beyerbach, 2000), and enhancing pre-service teachers'…”
Section: Six Refocusingmentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Research on Technology in Education,38(4), General education researchers have also suggested instructional approaches to embed within a single-course to enhance learning. One suggestion is to create a constructivist-based learning environment that promotes hands-on learning, collaboration, and modeling (Kang, Choi, & Chang, 2007). The merits of constructivist-based learning environments include: exposing pre-service teachers to authentic learning tasks (Murphy, 1997), improving pre-service teachers' perception of technology (Vannatta & Beyerbach, 2000), and enhancing pre-service teachers'…”
Section: Six Refocusingmentioning
confidence: 99%
“…According to Solomon and Schrum (2007), the emergence of technology in the 21 st century has fueled this need to transform education. Kang, Choi, and Chang (2007) Creating such an environment is critical to promote constructivist use of technology by pre-service teachers. Teo et al (2008) found that when the school environment does not align with constructivist-based learning principles it can have a profound influence.…”
Section: Constructivist Learningmentioning
confidence: 99%
“…E-Classes are n number of plus points but sometimes they create a lot of difficulties. These difficulties and problems associated with the leaner's behavior such as feeling boring and unengaging (Kang et al, 2007). Digital Learning has so much of the time and flexibility that learners never find the time to do.…”
Section: Theoretical Background Technology Acceptance Modelmentioning
confidence: 99%
“…Although there are different types of constructivism proposed by different theorists, most of the theories and approaches share common understandings of the epistemological beliefs and pedagogical perspectives. To illustrate, knowledge is constructed by individuals in the community of practice form one of the basis of these commonalities (Kang, Choi, & Chang, 2007). Lave and Wenger (1991) coined to the term communities of practice (CoP) so as to capture the importance of activity in binding individuals to communities and of communities to legitimizing individual practice.…”
Section: Constructivismmentioning
confidence: 99%